Expression of DNA repair and cell cycle control genes in HPV infection - E. V. Mashkina; V. V. Volchik; E. S. Muzlaeva; E. G. Derevyanchuk (Вавиловский журнал генетики и селекции)
One of the main etiological factors in the development of cervical cancer is infection with human papillomavirus (HPV). At the same time, the risk of developing a malignant process increases with an increase in viral load. The aim of this study was to investigate the transcription level of DNA repair and cell cycle control genes in the cervical epithelial cells of women with a clinically significant HPV viral load. The material for the study was DNA and RNA samples isolated from cervical epithelial cells in women. A total of 107 samples were analyzed. 55 women were HPV-positive (with a clinically significant viral load – more than 103 HPV genomes per 100 thousand human cells); the control group consisted of 52 HPV-negative women. All women were over 30 years old. The transcription level of the APEX1, ERCC2, CHEK2, TP53, TP73, CDKN2A, SIRT1 genes was determined using RT-PCR. It was shown that the detection frequency of the APEX1 and ERCC2 gene transcripts was increased in the group of women with a clinically significant viral load. The transcription level of all the studied genes did not differ between the control group and the group with clinically significant HPV concentrations. However, the transcription level of the TP53 and TP73 genes decreased with increasing viral load. In the control, a correlation between the transcription levels of genes involved in the functioning of the p53 protein was revealed. An increase in viral load during HPV infection is associated with a change in the coexpression of DNA repair and cell cycle control genes.